Jenis Hama Buah Kakao dan Tingkat Serangannya di Kota Payakumbuh, Sumatera Barat - Yudha, Pajri Ananta; Dwipa, Indra; Maulina, Fri (Jurnal Agroekoteknologi, 2025)
Cocoa is a main commodity in contributing to Indonesian foreign exchange. The main problem in cocoa cultivation is cocoa pod pest that could decrease production significantly. The research aimed to know the cocoa pod pests and attack level in Payakumbuh municipality. The study was conducted in Payakumbuh municipality and Laboraory of Pest, Faculty of Agriculture, Riau University from October to December 2023. Survey method was used in the study and purposive random sampling was used to determine the sampling. The criteria to determine the locations were ± 0.5 hectare of cocoa plantation and age of cocoa plant ± 4 years. According to criteria, 2 districts were chosen, Lamposi Tigo Nagari and Payakumbuh Timur. In each district, 5 sub-districts were chosen and in each sub-district, 2 cocoa plantations were chosen. The imaginary diagonal line was formed to determine the sampling plants. The result showed that there were four pests that attacked cocoa pod in Payakumbuh, Cocoa pod borer (CPB) (Conopomorpha cramerella), Helopeltis spp., rat and squirrel.The percentage of attacked plant by CPB was 10.60%,  percentage of attacked pod was 1.46% and attack intensity was 0.66%. For Helopletis spp., the percentage of attacked plant was 78.20%, the percentage of attacked pod was 57.75% and attack intensity was 37.50%. The percentage of attacked plant by rat and squirrel was 52.50% and the percentage of attacked pod was 42.17%.